1994
DOI: 10.1161/01.hyp.23.6.899
|View full text |Cite
|
Sign up to set email alerts
|

A kallikrein-like enzyme in the aorta of normotensive and hypertensive rats.

Abstract: We evaluated whether vascular kallikrein is altered in rats with genetic or experimental hypertension. Group 1 was infused intraperitoneally with angiotensin II (Ang II) or vehicle for 4 weeks; group 2 was injected subcutaneously with deoxycorticosterone (75 ^unol/kg once a week) or vehicle for 4 weeks; group 3 consisted of uninephrectomized rats on high sodium intake given deoxycorticosterone or vehicle; and group 4 consisted of spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats. Active and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The presence of tissue kallikrein in the blood vessels has been reported by many investigators (Madeddu et al, 1994;Nolly and Nolly, 1998;Nolly et al, 1994;Oza and Goud, 1992;Saed et al, 1990). The endogenous kinin may be generated by the tissue kallikrein-type proteases located in the vessels in the granulation tissues.…”
Section: Figurementioning
confidence: 68%
“…The presence of tissue kallikrein in the blood vessels has been reported by many investigators (Madeddu et al, 1994;Nolly and Nolly, 1998;Nolly et al, 1994;Oza and Goud, 1992;Saed et al, 1990). The endogenous kinin may be generated by the tissue kallikrein-type proteases located in the vessels in the granulation tissues.…”
Section: Figurementioning
confidence: 68%
“…24 Previous studies reported that 20% to 30% of the vascular kallikrein in the rat is present in the active form. 25,26 These combined results indicated that VSMCs contain a kallikrein-activating mechanism. However, the ratio of active versus inactive forms of recombinant human tissue kallikrein expressed in rat aorta after gene transfer remains to be evaluated.…”
Section: Discussionmentioning
confidence: 88%
“…Biochemical and histological studies indicate that kallikrein is expressed in human vascular wall, 31 and levels of expression seem to be variably affected in different forms of hypertension. 32 Preliminary immunohistochemical findings suggest that tK is also expressed in atherosclerotic carotid arteries (Madeddu P, unpublished results 2004). However, the absence of correlation with indicators of plaque instability favors the possibility that tK increases in peripheral circulation as a consequence of chronic hemodynamic changes related to the stenosis.…”
Section: Perspectivesmentioning
confidence: 98%